Maturação de sementes de aveia-preta (Avena strigosa Schreb). II. Maturidade da panícula e da espigueta - Nakagawa, J. (1994)
The present work aims at defining the panicle and spikelet maturity of Avena strigosa Schreb. Four experiments were carried out under field conditions during 1989 (E1 and E2) and 1990 (E3 and E4) in Botucatu county, São Paulo State, Brazil. The sowings were made in 04.19.89 (E1) and 06.18.89 (E2). Maturity of panicle was evaluated by weekly (E1) or biweekly harvests (E2) beginning at total emergence of the panicle. In E3 and E4, sowing was made in 06.04.90 and each experiment had a single harvest date (E3 = 11.01.90 and E4 = 11.07.90). After harvest, the spikelets with similar stage of development were grouped and evaluated. Based on dry matter accumulation and germination percentage of the seeds, it was observed that the maturity of the seeds in the panicle was reached at 28 and 35 days after total emergence of the panicle in the April sowing, and between 24.5 and 28 days in the June sowing. During this period a few percentage of panicles not yet yellow became all yellow, the cariopsis at semi-hard stage became hard and moisture of the seeds dropped from 32% to 12%. The maturity of the seeds in the spikelet was reached when the glumes changed their color from yellowish to yellow, the lemma and palea changed from yellow with black strips to black, the cariopsis changed from farinaceous stage to semi-hard and the moisture content of the seeds changed from 40% to 25%.